Reinoculação de rizóbio em diferentes estádios de crescimento do feijoeiro - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The bean crop is admittedly demanding nitrogen, with mineral fertilization being the main supply to plants today. However, the availability of more efficient inoculants on the market, containing strains of R. tropici potentially more efficient in fixing atmospheric N2, can replace the use of nitrogen fertilizers, as long as some existing bottlenecks in the application methodology are overcome, for example, guaranteeing the existence of active nodules in the most demanding phases of the crop. Thus, this work aimed to investigate the response capacity of bean plants, BRS FC402 cultivar, submitted to re-inoculating Rhizobium cells in topdressing, applied in different stages of plant growth, in the edaphoclimatic conditions from the Cerrado. Two experiments were implemented, one in a greenhouse (CRD) and another in the field (RBD) in the 2020/2021 harvest, in the rainy season, with four replications. The following treatments were evaluated in both experiments: T1 = non-inoculated - control; T2 = inoculation via seed (VS); T3 = VS + re-inoculation at the V4 stage; T4 = VS + re-inoculation at the R5 stage; T5 = VS + re-inoculation at the R6 stage; T6 = VS + re-inoculation at the V4 and R5 stages; T7 = VS + re-inoculation at the V4 and R6 stages; T8 = VS + re-inoculation at the R5 and R6 stages; T9 = VS + re-inoculation at the V4, R5, and R6 stages, and T10 = mineral nitrogen fertilization. The greenhouse experiment was carried out until the R7 stage, with an evaluation of the variables referring to nodulation and plant morphology, while the field experiment was carried out until the end of the cycle, with the assessment of the nodulation and morphological variables at the R7 stage. and agronomic variables at the R9 stage, at harvest time. The accomplishment of the study made it possible to obtain the following conclusions: The use of re-inoculation of rhizobium cells in topdressing, besides the inoculation at sowing via seed, positively influenced the bean nodulation process. The morphological characteristics of bean plants showed good development with the supply of N performed by inoculation and re-inoculation in topdressing, equivalent to the addition of mineral nitrogen fertilizer. The topdressing re-inoculation at the reproductive stages, R5 to R7, did not prove to be efficient in supplying N to the bean crop. Inoculation applied via seed associated with re-inoculation in topdressing at the V4 stage provided a higher grain yield of the bean crop, being able to replace the use of mineral nitrogen fertilizer.
Reinoculation of rhizobia in different growth stages of common bean
Keywords: P. vulgaris; Nutrição de planta; FBN; Acúmulo de biomassa.; Rendimento; Biomassa; Feijão - Feijoeiro; P. vulgaris; Plant nutrition; NBF; Biomass accumulation; Yiel; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA